Pervaporation of ethanol-water mixture using PVA zeolite-clay membranes - Lee, Kha Ling; Mohd Nawawi, Mohd Ghazali; Sadikin, Aziatul Niza (Penerbit UTM Press, 2008)
The objective of this research is to study the effects of feed concentration and temperature on the pervaporation of ethanol-water mixtures using polyvinyl alcohol (PVA) zeoliteclay membranes. The liquid feeds for the pervaporation were prepared using different weight concentrations of ethanol which were 10 wt%, 30 wt%, 50 wt%, 70 wt% and 90 wt% of ethanol. The pervaporation separations were conducted at different temperatures which were 30, 40, 50, 60 and 70 Â°C. The PVA zeolite-clay membranes were prepared by dissolving 0.2 wt% zeolite-clay powder and 5 wt% PVA powder in distilled water. The solution was casted on a porous support to produce composite membrane. The support layers were produced through phase inversion process using casting-solution of 12 wt% polysulfone, 11 wt% methyl cellusolve and 77 wt% N,N-dimethylformamide (DMF). The membranes were used for the separation of ethanol-water mixtures via pervaporation. The results showed that, when the ethanol concentrations of feed and feed temperature increased, the selectivity increased but absorption (flux) decreased. The PVA zeolite- clay composite membranes were relatively hydrophilic, mechanically strong and thus suitable to be used for the pervaporation separation of ethanol-water mixtures.